2011
DOI: 10.5539/jedp.v1n1p133
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Preservice Teachers’ Self-Efficacy: From Science Methods to Student Teaching

Abstract: The purpose of this research was to assess preservice teachers self-efficacy at different stages of their educational career in an attempt to determine the extent to which self-efficacy beliefs may change over time. In addition, the critical incidents, which may contribute to changes in self-efficacy, were also investigated. The instrument used in the study was the Teaching Science as Inquiry (TSI) Instrument. The TSI Instrument was administered to 38 preservice elementary teachers to measure the self-efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Compared to international averages, teachers spent 29% less time on science teaching per year in Grades 4 and 5 and 47% less time in Grades 8 and 9 . In comparison with general CAS, engaging students in complex and authentic inquiry learning is time-consuming in nature, and lack of time has been a common area of concern for many teachers (Murphy et al, 2007;Smolleck and Mongan, 2011;Chichekian and Shore, 2016). Previous studies have demonstrated the effectiveness of inquiry activities as a basis for quality teaching to enhance science achievement (e.g., .…”
Section: The Role Of Teacher Self-efficacy and Perceived Time Constramentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to international averages, teachers spent 29% less time on science teaching per year in Grades 4 and 5 and 47% less time in Grades 8 and 9 . In comparison with general CAS, engaging students in complex and authentic inquiry learning is time-consuming in nature, and lack of time has been a common area of concern for many teachers (Murphy et al, 2007;Smolleck and Mongan, 2011;Chichekian and Shore, 2016). Previous studies have demonstrated the effectiveness of inquiry activities as a basis for quality teaching to enhance science achievement (e.g., .…”
Section: The Role Of Teacher Self-efficacy and Perceived Time Constramentioning
confidence: 99%
“…Teachers often feel a lack of confidence in enacting CAS in their practice (Murphy et al, 2007). These student-centered approaches are also demanding for teachers as they tend to be more timeconsuming (Murphy et al, 2007;Powell-Moman and Brown-Schild, 2011;Smolleck and Mongan, 2011;Wang, 2011;Chen and Wei, 2015). Although previous research has indicated that teachers who feel confident in their teaching abilities are more likely to develop challenging lessons (Holzberger et al, 2014;Depaepe and König, 2018), it has not yet become clear how both teachers' self-efficacy and the perceived time constraints are related to the implementation of CAS.…”
Section: Introductionmentioning
confidence: 99%
“…Bursal (2007) suggested that this course should include professional experience as well as the activities in the science teaching course to increase the science teaching self-efficacy of the prospective classroom teachers. Similarly, Smolleck and Mongan (2011) have observed that well-planned science methods and teaching practice experience have improved the science teaching self-efficacy of prospective classroom teachers.…”
Section: Discussionmentioning
confidence: 87%
“…Based on this method, people, events, objects or cases who/which meet the pre-defined qualities would then be selected to answer the research question [55].In this research, the first criterion was the grade of the participants. As the processes experienced in teacher training programs are effective on the pre-service teachers' self-efficacy beliefs [56][57][58][59], and motivation towards teaching profession [60,61], the senior pre-service history teachers who were closer to graduation were selected as participants.…”
Section: Participantsmentioning
confidence: 99%